BACTERIAL DYSENTERY DISEASE GENERAL DESCRIPTION, ETIOLOGY, EPIDEMIOLOGY, PREVENTION AND MEASURES AGAINST EPIDEMICS - Mizrobov Doston Oktamovich (World Scientific Research Journal, 2025)
Abstract: Shigellosis (bacterial dysentery) is an anthroponotic infectious disease with a fecal-oral transmission mechanism. It is caused by bacteria of the genus Shigella, and occurs in acute and chronic forms. It is characterized by manifestations of general intoxication with fever and signs of inflammation of the gastrointestinal tract (mainly the distal colon in the form of spastic hemocolitis).This article describes the general description of shigellosis, their etiology, epidemiology, diagnostic and treatment methods, as well as ways to improve preventive and anti-epidemic measures. The article analyzes the main trends in reducing the spread of infectious diseases based on world experience and modern approaches.